The Effect of Islamic Financial Literation And Financial Technology On Islamic Financial Inclusion - Basrowi Basrowi; Tulus Suryanto; Erike Anggraeni; Muhammad Nasor (AL-FALAH : Journal of Islamic Economics, 2020)
Purpose: The purpose of this study was to determine the magnitude of the influence of Islamic financial literacy and Islamic financial technology on the inclusion of Islamic finance in students in Lampung Province both partially and simultaneously.Design Methods:The method used is a survey method. The population of this study is all smester V students and above in Islamic Economics Study Program, Islamic Banking. and sharia accounting in all State and Private Universities in Lampung Province, totaling 3080 people. The sampling technique used is proportional grain sampling, as much as 10% of the population of 308 people. Data collected using surveys, with google form. The collected data were analyzed using simple and multiple regression analysis.Findings:Based on the results of the analysis it can be concluded, first, there is a positive and significant influence between the literacy of Islamic finance on Islamic financial inclusion. Second, there is a positive and significant influence between Islamic financial technology on Islamic financial inclusion. Third, there is a positive and significant influence between Islamic financial literacy and Islamic financial technology together on Islamic financial inclusion.Originality Value: Of the two independent variables, sharia financial literacy variables contributed more than sharia financial technology variables to sharia financial inclusion.